[OP.4C.01] ANTIHYPERTENSIVE DRUG TREATMENT FAILS TO NORMALIZE SYMPATHETIC ACTIVITY: MICRONEUROGRAPHIC EVIDENCE AND CLINICAL IMPLICATIONS. (September 2016) - Seravalle, G.L.; Brambilla, G.; Dell'Oro, R.; Trevano, F. Quarti; Pizzala, D. Prata; Ravaro, S.; Mancia, G.; Grassi, G.
Abstract : Objective: It is unknown whether and to what extent antihypertensive drug treatment capable to reduce adrenergic overactivity normalizes cardiovascular sympathetic drive. Design and method: Results of three studies carried out by our group assessing muscle sympathetic nerve traffic (MSNA) via the microneurographic technique were analyzed, comparing the data obtained after long-term combination drug treatment with ACE-inhibitors, diuretics and calcium channel blockers with those detected in 30 age-matched untreated healthy normotensive controls (C). A total of 78 middle-age treated hypertensive patients (HTs) were analyzed. Average follow-up amounted to 10 weeks. Results: At baseline, before treatment, clinic and ambulatory blood pressure (BP) values were as expected significantly greater in HTs than in C. This was the case also for MSNA (62.4 ± 1.4 vs 35.1 ± 1.8 bursts/100 heart beats, p < 0.01). Drug treatment significantly reduced BP to values <140/90 mmHg and <125/79 mmHg for clinic and ambulatory data respectively. MSNA values were also significantly reduced. In no study, however treatment was capable to bring back to normal MSNA values, which remained significantly greater than controls both when ACEI-diuretic, ACEI/calcium antagonists and angiotensin II receptor blockers/diuretic combination treatment was used (51.3 ± 2.7, 49.4 ± 2.3 and 44.5 ± 2.4 bursts/100 heart beats, p < 0.05 at least vs C). Conclusions: Our study provides the first evidence that antihypertensive combination drug treatment, although allowing to achieve normal BP values, fails to normalize sympathetic activity, independently on the type of drugs used. This lack of normalization might contribute to determine the so-called residual risk of treated hypertensive patients.